Measurement and reporting of climate-smart agriculture: technical guidance for a countrycentric process - Nowak, Andreea C.; Wilkes, Andreas; Rosenstock, Todd S. (2019)
Given the extent of climate-smart agriculture (CSA) initiatives at project, national, regional and global levels, there is increasing interest in tracking progress in implementing CSA at national level. CSA is also expected to contribute to higher-level goals (e.g., the Paris Agreement, Africa Union’s Vision 25x25, and the Sustainable Development Goals [SDGs], etc.). Measurement and reporting of climate-smart agriculture (MR of CSA) provides intelligence on necessary the status, effectiveness, efficiency and impacts of interventions, which is critical for meeting stakeholders’ diverse management and reporting needs. In this paper, we build the case for a stakeholder-driven, country-centric framework for MR of CSA, which aims to increase coordination and coherence across stakeholders’ MR activities, while also aligning national reporting with reporting on international commitments. We present practical guidance on how to develop an integrated MR framework, drawing on findings from a multi-country assessment of needs, opportunities and capacities for national MR of CSA. The content of a unified MR framework is determined by stakeholders’ activities (how they promote CSA), needs (why MR is useful to them) and current capacities to conduct periodic monitoring, evaluation and reporting (how ready are institutions, staff and finances). Our analysis found that explicit demand for integration of data systems and active engagement of stakeholders throughout the entire process are key ingredients for building a MR system that is relevant, useful and acted upon. Based on these lessons, we identify a seven-step framework for stakeholders to develop a comprehensive information system for MR of progress in implementing CSA.